The Effect of Water on the Tin Electrodeposition from [Bmim]HSO4 Ionic Liquid - Jie Tang; DongLiang Lv; CunYing Xu; YiXin Hua; QiBo Zhang; PingZhao Niu; XiaoLin Zhu (International Journal of Electrochemistry)
The electrodeposition of tin from SnO in ionic liquid 1-butyl-3-methylimidazolium hydrogen sulfate ([Bmim]HSO4) in the presence of water at different cathodic potential was investigated. With the addition of water to [Bmim]HSO4 ionic liquid, the electrochemical window of the electrolyte decreases and the reduction potential of Sn(II) positively shifts. The water content of ionic liquid electrolyte has a distinct effect on morphology of the deposits. As water content increased from 0 to 50% (v/v), the morphology of deposits varies from granular to hexagonal rod-like, then to hollow tubular, and finally to wire-like. The XRD phase analysis showed that both Sn and CuSn alloys were deposited in ionic liquid/water mixtures. However, in dried ionic liquids only Cu3Sn was obtained, surprisingly. The difference in the structure might be attributed to the various interactions of the ions with the Cu substrate. In addition, the deposition potential was found to play a significant role in the morphology of deposits.